Reactive Transformation and Increased BDNF Signaling by Hippocampal Astrocytes in Response to MK-801. - Wenjuan Yu; Hao Zhu; Yueming Wang; Guanjun Li; Lihua Wang; Huafang Li (PLoS ONE)
MK-801, also known as dizocilpine, is a noncompetitive N-methyl-D-aspartic acid (NMDA) receptor antagonist that induces schizophrenia-like symptoms. While astrocytes have been implicated in the pathophysiology of psychiatric disorders, including schizophrenia, astrocytic responses to MK-801 and their significance to schizotypic symptoms are unclear. Changes in the expression levels of glial fibrillary acid protein (GFAP), a marker of astrocyte activation in response to a variety of pathogenic stimuli, were examined in the hippocampus of rats treated with the repeated MK-801 injection (0.5 mg/10 ml/kg body weight for 6 days) and in primary cultured hippocampal astrocytes incubated with MK-801 (5 or 20 μM for 24 h). Moreover, the expression levels of BDNF and its receptors TrkB and p75 were examined in MK-801-treated astrocyte cultures. MK-801 treatment enhanced GFAP expression in the rat hippocampus and also increased the levels of GFAP protein and mRNA in hippocampal astrocytes in vitro. Treatment of cultured hippocampal astrocytes with MK-801 enhanced protein and mRNA levels of BDNF, TrkB, and p75. Collectively, our results suggest that hippocampal astrocytes may contribute to the pathophysiology of schizophrenia symptoms associated with NMDA receptor hypofunction by reactive transformation and altered BDNF signaling.